Essential oils : all-natural remedies and recipes for your mind, body, and home - Curtis, Susan (Homeopath); Thomas, Pat, 1959-; Johnson, Fran (Cosmetic scientist) (DK Publishing, 2016)
"Introduce yourself to the world of Essential Oils for treating maladies and improving mental and physical well-being. Featuring comprehensive profiles of 88 essential oils, all-natural remedies for common ailments, aromatic recipes for home and beauty, and helpful guidance for blending, storing, and using essential oils, this introductory guide is packed with authoritative information from the experts at Neal's Yard Remedies,"--Amazon.com.